2015
DOI: 10.1021/jp511908t
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Absorption Studies on Mixed Alkali Orthosilicates Containing Rare-Earth Second-Phase Additives

Abstract: Lithium silicate containing eutectic orthosilicate mixtures developed by a solid-state route displayed excellent characteristics as carbon dioxide absorbents at elevated temperature, showing absorption capacity of 256 mg g −1 . Incorporation of second-phase materials was investigated as a strategy to enhance the stability of the absorbent materials against agglomeration and sintering during powder processing and high-temperature cyclic absorption/desorption loading. Yttrium oxide, gadolinium oxide, and lanthan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…[1][2][3] The selective adsorption of CO 2 from industrial gaseous wastes and flue gases, followed by its recycling/removal, is therefore a research topic of prime importance. [4][5][6][7][8][9][10] The inherent ability of amine solutions to capture CO 2 selectively from flue gas through the absorption between amine and CO 2 molecules is well established in the literature. [11][12][13][14] However, the handling and corrosion issues associated with the use of liquid amines and the loss of liquid amine at working temperatures remain the main drawbacks of these kinds of materials.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The selective adsorption of CO 2 from industrial gaseous wastes and flue gases, followed by its recycling/removal, is therefore a research topic of prime importance. [4][5][6][7][8][9][10] The inherent ability of amine solutions to capture CO 2 selectively from flue gas through the absorption between amine and CO 2 molecules is well established in the literature. [11][12][13][14] However, the handling and corrosion issues associated with the use of liquid amines and the loss of liquid amine at working temperatures remain the main drawbacks of these kinds of materials.…”
Section: Introductionmentioning
confidence: 99%
“…However the use of high temperature can induce compositional changes due to the sublimation of lithium during irradiation leading to poor absorption and kinetics during the sorption process. We have earlier reported the synthesis of Li 4 SiO 4 through microwave assisted sol-gel process resulting in the formation of Li 4 SiO 4 nano-rods that displayed near theoretical absorption capacity with enhanced sorption rates [31][32] . However, the CO 2 absorption properties of the pure Li 4 SiO 4 powder were found insignificant below 450 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Kato and Nakagawa first synthesized Li 4 SiO 4 from Li 2 CO 3 and SiO 2 precursors via a solid‐state reaction route. In later studies, identifying potential silicon sources and Li precursors , emerging synthesis routes (impregnated suspension , precipitation , carbon templating , and sol‐gel methods ), and the incorporation of hetero elements into the Li 4 SiO 4 crystal structure have been substantially used to prepare effective Li 4 SiO 4 sorbents. Despite these improvements in capture capacity, most sorbents still suffer from slow kinetics at low CO 2 partial pressures .…”
Section: Introductionmentioning
confidence: 99%
“…The particle size/pore structure of the sorbent, doped elements, adsorption temperature, and flue gas components all play essential roles in the adsorption reaction, thereby making the specific mechanisms significantly complex. For CO 2 adsorption on pure Li 4 SiO 4 , it has been widely reported that rapid and chemically controlled chemisorption is followed by slow Li + and O 2‐ diffusion, which was based on shrinking core, double‐exponential, and Avrami–Erofeev models . According to this mechanism, small‐sized sorbents reduced the diffusive limitations, allowing Li 4 SiO 4 to achieve fast diffusion; meanwhile, higher surface areas improved the chemisorption process.…”
Section: Introductionmentioning
confidence: 99%